Evidence of weight loss in junior female judo athletes affects their development - Yoshida, Ena; Hayashida, Harumi; Sakurai, Tomonobu; Kawasaki, Kenzo (Frontiers in Sports and Active Living, 2024)
Purpose: The facile manipulation of body weight in junior athletes has the potential to pose significant risks to their lifelong health. In judo, which is a weight class sport, pre-competition weight loss is widespread even among juniors, but information on the current situation is scarce, especially for female athletes, for whom it is important to provide adequate nutrition and enhance bone mass during the growth period, and the details of the current situation are not clear. Therefore, the purpose of this study was to determine the actual weight loss during the growth period in junior female judo athletes and its subsequent impact on their health. Methods: The survey was a cross-sectional survey of junior female judo athletes in Japan using a questionnaire. Participants were asked to respond via an online questionnaire about their weight, height, weight loss experience, menstruation, competition results, and other lifestyle. Results: 51.8% of subjects experienced weight loss for competition during their junior high school years (ages 12-15). Those who experienced weight loss during secondary sexual characteristics were found to be significantly shorter in current height than those who did not (p< 0.05). Weight loss during secondary sexual characteristics did not affect current menstrual cycle. There was no significant difference in competition results due to the experience of weight loss during junior high school (χ² = 4.485, df = 3, n.s.). Conclusions: These findings suggest that weight loss during the growth spurt phase may adversely impact normal development. It also suggested that weight loss during the junior high school years may not be a strategy to bring about better competition results. These observations indicate the need for education on appropriate class selection and weight control for junior athletes in weight class competitions